Inclined and gradient Al component AlGaN nanostructures with enhanced photoelectric performance for solar-blind UV detectors. (1st February 2022) - Lv, Zhisheng; Liu, Lei; Sun, Yan; Zhangyang, Xingyue; Lu, Feifei; Tian, Jian
Abstract: This paper designs an AlGaN nanoarray model with different Al composition distributions, and studies the effects of geometric parameters on its optical response and quantum efficiency. COMSOL Multiphysics software was used to calculate and analyze the influence of the axis inclination on the light absorption efficiency and light field distribution of the nanostructures. Compared with vertical nanostructures, tilted structure arrays have better light absorption characteristics, and the photoelectric response of gradient Al composition AlGaN photocathode is more significant at the wavelength region of 200–300 nm. Simulation studies have found that the dense nanostructured array will reabsorb part of the emitted electrons, and the use of an auxiliary external electric field can effectively improve the collection efficiency of the photocathode. Finally, when the external electric field is 2.5 V/μm, the nanowire height is 800 nm and the incident angle is 10°, the GaN-Al0.365 Ga0.635 N layered nanostructure array can achieve an electrical response efficiency of 30.93%. Highlights: An inclined Alx Ga1-x N nanostructured photocathode is proposed as light-trappers for solar-blind UV detectors. Optical absorption, quantum efficiency and collection efficiency of inclined AlxGa1-xN photocathodes is discussed. The optimal light absorption of Al composition AlGaN nanowire array with optimal structural parameters can reach 99%. The optimal collection efficiency of the Alx Ga1-x N photocathode can even reach 31.99%.